(untitled) (Web of Teachers: Inderscience Research, 2023)
Land is one of the most important assets for agricultural farmers. Therefore, optimal use of agricultural land is necessary. This study aims to obtain the optimal composition of land use for maximum income. The optimization method used in this study is linear programming models. According to the results of the analysis, the rice area is 135,314 ha, the corn area is 11,798 ha, the soybean area is 2,290 ha, the land use structure for peanut cultivation is 2,818 ha, and the value of the farmers’ income is 2,68000.0 thousand rubles. ,-/year. The results of this analysis can be considered by farmers when making decisions about cropping methods.